1999
DOI: 10.1111/j.1553-2712.1999.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Factors on Emergency Medicine Resident Career Choice

Abstract: Abstract. Objective: To evaluate the impact of environmental factors on emergency medicine (EM) resident career choice. Methods: Program directors of all U.S. EM residencies were surveyed in November 1997. A 22-item questionnaire assessed resources allocated to research, fellowship availability, academic productivity of faculty and residents, and career choices of residency graduates. Results: The response rate was 83%. The program director (mean Ϯ SD) estimates of resident career choice were as follows: 27.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
(16 reference statements)
1
28
1
Order By: Relevance
“…8,9 In contrast, expressed interest among my own trainees runs about 10:1 in favor of critical care.…”
mentioning
confidence: 84%
“…8,9 In contrast, expressed interest among my own trainees runs about 10:1 in favor of critical care.…”
mentioning
confidence: 84%
“…4,5 If those graduates stick to their plans, this results in a fairly small annual pool of around 50 to 70 committed new researchers per year. The number of EM graduates who enter research fellowships each year can be counted digitally-with fingers, not a computer.…”
Section: Why Are We Refraining From Research Training?mentioning
confidence: 99%
“…Despite the fact that in 1997 only 29% of residency program directors thought that their residents were well prepared for an academic career that required original research, only 25% of 1997 EM graduates who were entering an academic career believed that fellowship training was important for academic success. 4,5 Why, in the face of good evidence that research training strongly correlates with a successful research career, does EM shun such training? 6 The reasons are multifactorial: few funded fellowship opportunities in EM, the large debt burden faced by many graduating residents, and a lack of exposure to research role models.…”
Section: Why Are We Refraining From Research Training?mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In a survey of program directors of all U.S. EM residencies, only 29% of respondents indicated that they believed their residents were well prepared for an academic career that requires original research. 6 Similarly, in a survey of practicing emergency physicians, academic faculty cited insufficient research training and finding knowledgeable collaborators as significant obstacles to research productivity. 7 This sense of ill preparedness for academic medicine without significant postgraduate training is not likely an illusion.…”
mentioning
confidence: 99%